Does servant leadership behavior induce positive behaviors? a conceptual study of servant leadership, psychological safety and turnover intention - Brohi, Noor Ahmed; Jantan, Amer Hamzah; Mehmood, Sultan Adal; Khuhro, Mansoor Ahmed; Aktar, Muhammad Saood (Science Publishing Corporation, 2018)
In this paper, we examine how servant leadership and psychological safety may enlighten our understanding of human mechanisms that affect follower outcomes. Servant leadership style as penned by Robert Greenleaf that servant leaders guide followers to adopt the behavior of their leaders by putting others needs above their own. From emerging research on servant leadership, we proposed a model contending that servant leaders increase employees’ psychological safety that organization is a safe place to speak up ideas, opinions and take decisions, which directly influences Employees’ turnover intention. As proposed, servant leadership will be negatively related to Employees’ turnover intention and positively related to psychological safety. Psychological safety will mediate the relationship between servant leadership and turnover intention.